FEERs and Uncertainty : Confidence Intervals for the Fundamental Equilibrium Exchange Rate of the Canadian Dollar - Kramer, Charles (IMF Working Papers; Working Paper, 1996)
Models of Fundamental Equilibrium Exchange Rates (FEERs) impose internal and external balance, and so appeal to fundamental notions of equilibrium from a macroeconomic perspective. However, the need to estimate internal and external imbalances creates uncertainty in the approach. Parameters must be estimated, and equilibrium balances must be gauged using judgement. Hence it makes sense to consider the FEER as a statistical estimate rather than a fixed number, and to calculate confidence intervals for the FEER. This paper calculates such confidence intervals with data for Canada, under a variety of assumptions. The estimated confidence intervals are quite wide, principally because of uncertainty about price elasticities in the underlying trade equations.